`Failure analysis of short-circuit failure of metal-oxide-metal capacitor. (October 2022) - Wang, Yan; Zhu, Qingguo; Huang, Caiqing
Abstract: Metal-oxide-metal (MOM) capacitors are used widely in semiconductor integrated circuits. This study describes a method for failure analysis of MOM capacitor short-circuit. We present two case examples to highlight the significance of this method. Various techniques are described, such as thermal emission microscopy (ThEM), beam induced resistance change (OBIRCH), photoemission microscopy (PEM), focused ion beam (FIB), and passive voltage comparison (PVC). ThEM could be an effective alternative, albeit with low magnification. OBIRCH could help verify the defect location in the MOM structure, albeit with a large region of interest (ROI). The application of PEM based on an InGaAs detector can reduce the ROI and yield satisfactory fault isolation results. PVC can indicate the metal bridge phenomenon and help guide FIB cross-sectional analysis. To summarize, our observations indicate that PEM and PVC are effective alternatives for the failure analysis of MOM short-circuit failure. Highlights: This work focuses on how to perform a MOM short analysis efficiently. The ROI (region of interest) is reduced to 5x5um using PEM while OBIRCH with large ROI in a linear shape, which is ideal for physical analysis. PVC (Passive Voltage Contrast) phoneme indicated the bridge defectduring the FIB cross-section analysis. The new method suggests PEM & PVC are effective alternatives in the failure analysis of short circuit MOM.